The Association of rs1670533 Polymorphism in RNF212 Gene With the Risk of Down Syndrome in Young Women - Davari-Tanha, Fatemeh (J Family Reprod Health, 2018)
Objective: To evaluate association between polymorphism rs1670533 in RNF212 gene with the risk of Down syndrome in young women. Materials and methods: In a case control study, one hundred pregnant women were evaluated in both group. The case group consisted pregnancy with diagnosis of Down syndrome in women younger than 35 years old. The control group consisted pregnancy with normal neonate. Fifty pregnant women in each group were allocated.one hundred blood samples were collected. Genomic DNA was extracted by salting – out method and polymorphism of rs1670533 were detected by PCR.PCR products were detected on 2% agarose gel electrophoresis. Results: The TTrs1670533 haplotype was present in 36% of pregnant women with Down syndrome versus 14% of normal pregnant women, (p = 0.003 e-12; CI 95%1.665-5.305, OR = 3.107); TC haplotype was present in 56% of normal pregnancy regarding of16% of pregnancy with Down syndrome (p = 4.288 e = 12; CI 95%: 0.145-0.25; OR = 0.126). Conclusion: It seems that TTrs1670533 haplotype is a risk factor for pregnancy with Down syndrome in young women and TC haplotype has protective effect.